Strategic quality assurance - Tapiero, Charles S. (Journal of Business Economics and Management, 2006)
The purpose of this paper is to provide a strategic (game) approach to Quality Assurance. Unlike previous approaches that presume non‐motivated sources of risk, we assume in this paper that risk may arise strategically due to other motivations. For example, problems associated to supply risks received by a producer‐buyer. As a result, strategic quality assurance problems are formulated in terms of random payoff game which we solve while using the traditional approach to risk specification imbedded in quantile risks (Type I and Type II errors in statistics or producers and consumers risks). Technically, the approach devised consists in solving risk constrained (random payoff) games which involve strategic partners, potentially in conflict. The approach devised is then applied to a number of problems spanning essentially mutual sampling (quality assurance) between a buyer and supplier and strategic quality control in supply chains where potential conflict and information and power asymmetry is an inherent part of the operational problem to be dealt with. In such circumstances, contracts agreements might be violated if the parties do not apply strategic control tools to assure that what was intended is actually performed. First published online: 14 Oct 2010